The Role of Hand Hygiene Compliance in Preventing Diseases - Badr Mohammad O Al Omair; Fadiyah Khalid Shaman Alrubudh; Maliyaha Sbeel Almutairi; Elham Ahmed Alshehri; Najla Mohammed A Alswean; Mada Hamad M Alharbi; Fakhra Yahya Kaabe; Abdullah Fahad Fayez Al Dosari; Taghreed Abdullah Ayed Alenezi; Haifa Ali Gharawi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Infections transmitted via the hands of healthcare workers are responsible for tens of millions of patient deaths every year. However, this can be prevented by the life-saving act of hand hygiene. It is concluded that ways must be found to ensure compliance with hand hygiene in the hospital scenario, as specific training and sensitization are recognized as obstacles to adherence. Mention can also be made of factors such as work overload and limited staff, which restrict hygiene. Strict adherence to hand hygiene is the only solution to mitigate this preventable infection. However, adherence does not always guarantee the effectiveness of the activity. Hand hygiene practices contribute to the reduction of cross-infection, especially of multi-resistant microorganisms, being simple, effective, and inexpensive measures, which can be harmful to preventing them from performing well, thus requiring the implementation of new strategies that aim for safe and responsible health habits. Actions should be taken by the health team in the promotion of hand hygiene, as their perception of patient safety is critical to modifying their care habits. It should also be emphasized that hand hygiene should be provided to visitors at the hospital, as their compliance can reduce the risk of hospital-acquired infections, contributing to the safety of individuals living in this environment. Currently, programs are available that teach the basic steps and importance of correct hand hygiene. This review aims to address the roleof hand hygiene compliance in preventing diseases.